Regional outburst prevention technology of pre-drainage gas area in west well area of sihe coal mine - Zhang, Peng (Frontiers in Energy Research, 2023)
Coal and gas outburst is one of the main factors affecting the safe and efficient production of coal mines. With the increase of mining depth and mining speed, the dynamic phenomena of coal and gas outburst will become more and more serious. Through the study of various outburst prevention measures in the pre-drainage gas area such as surface drilling, bedding (directional) drilling, and crosslayer drilling, combined with the coal seam occurrence and mining technology of the West Mine Area, a feasible regional pre-drainage comprehensive outburst prevention mode suitable for the characteristics of the 3# coal seam in the West Mine Area has been obtained. This mode is based on pre-pumping of surface drilling first, directional long borehole along the reservoir and pre-pumping of cross-zone borehole, which provides reliable guarantee for safe and efficient production in outburst well area.